CORPORATE INTERNET REPORTING: DITINJAU DARI UKURAN PERUSAHAAN, KINERJA KEUANGAN, LEVERAGE, DAN KEPEMILIKAN INSTITUSIONAL - Wati, Kharisma Dheni; Citradewi, Adelina (Jaksya: Jurnal Akuntansi Syariah, 2025)
This research aims to determine the role of company size, financial performance, leverage, and institutional ownership on corporate internet reporting. This research uses a type of library research. This research uses a quantitative approach by utilizing secondary data in the form of company annual financial reports. The population in this research is all companies in the basic industrial and chemical sectors registered on the IDX in 2022, totaling 91 companies. Sampling used a purposive sampling method and a total sample of 44 companies was obtained. Data analysis techniques use descriptive statistical analysis, classical assumption testing, multiple linear regression analysis, and hypothesis testing. The research results state that the variable that influences corporate internet reporting is company size, while the variables that do not influence corporate internet reporting are financial performance, leverage and institutional ownership.